Analysis of research fields involving wastewater-based epidemiology and interdisciplinary spillovers using a structural topic model - Michio Murakami; Yoshitaka Nishikawa; Masaaki Kitajima (Results in Chemistry)
To further the academic development and practical application of wastewater-based epidemiology (WBE), a greater understanding of its impact across various research fields, academic disciplines, and interdisciplinary spillovers is required. However, no previous studies have applied the structural topic model to WBE papers to characterize different topics or to study the interdisciplinary spillover effects between topics. Therefore, we used a structural topic model to provide an overview of the topics involved in WBE in various research fields and elucidate their characteristics. The topics in the literature cited by high-impact papers and the literature citing high-impact papers were also analyzed to identify spillovers in WBE research between fields. A total of 2842 papers were extracted using Scopus on July 3, 2023, and classified into 5 topics related to WBE using the structural topic model, with the manual exclusion of topics highly relevant to non-WBE papers. WBE topics included “illicit drugs,” “SARS-CoV-2 detection,” “virus and genotype,” “public health and COVID-19,” and “COVID-19 and clinic.” The average publication years for “virus and genotype” and “illicit drugs” were 2017 and 2019, which were earlier than those of COVID-19-related papers (2020–2022). Furthermore, “virus and genotype” had fewer papers (N = 241) and citations (arithmetic mean, 21.8), whereas “illicit drugs” had a higher number of papers (N = 475) and citations (32.3). Although research on COVID-19 has only recently begun, “SARS-CoV-2 detection” had a higher number of papers (N = 348) and citations (32.8). Analysis of the sources and effects of high-impact papers on each topic showed that public health-driven studies referred to numerous illicit drugs and created connections with subsequent COVID-19-related papers. Studies that link existing research fields with future risk factors for major public health crises indicate the direction for innovative interdisciplinary research.